A Generic Strategy to Generate Bifunctional Two-in-One Antibodies by Chicken Immunization - Harwardt, Julia; Bogen, Jan P.; Carrara, Stefania C.; Ulitzka, Michael; Grzeschik, Julius; Hock, Björn; Kolmar, Harald (Frontiers in Immunology, 2022)
Various formats of bispecific antibodies exist, among them Two-in-One antibodies in which each Fab arm can bind to two different antigens. Their IgG-like architecture accounts for low immunogenicity and also circumvents laborious engineering and purification steps to facilitate correct chain pairing. Here we report for the first time the identification of a Two‐in‐One antibody by yeast surface display (YSD) screening of chicken-derived immune libraries. The resulting antibody simultaneously targets the epidermal growth factor receptor (EGFR) and programmed death‐ligand 1 (PD-L1) at the same Fv fragment with two non-overlapping paratopes. The dual action Fab is capable of inhibiting EGFR signaling by binding to dimerization domain II as well as blocking the PD-1/PD-L1 interaction. Furthermore, the Two-in-One antibody demonstrates specific cellular binding properties on EGFR/PD-L1 double positive tumor cells. The presented strategy relies solely on screening of combinational immune-libraries and obviates the need for any additional CDR engineering as described in previous reports. Therefore, this study paves the way for further development of therapeutic antibodies derived from avian immunization with novel and tailor-made binding properties.